The Construction of Alternatives to Hegemonic Forms of Agrarian Production: Reflections from Argentina and Chile - Palmisano, Tomás (2023)
This article has two research objectives: 1) To analyze the motivations that the subjects expose to explain the construction and sustainability of agri-food alternatives; 2) To identify the tensions, conflicts, and violence of agribusiness in the face of which they construct these alternative approaches. Our methodological approach of Qualitative Content Analysis is used in combination with socio-productive information on the subjects and the agricultural context in which they are inserted. Fieldwork was conducted between 2017 and 2023 in Buenos Aires and La Rioja (Argentina) and Putaendo (Chile). The findings of the analysis contribute to a qualitative and relational understanding of both the motivations and the contextual conditions that shape them. Among the main elements mentioned by the people interviewed, the following stand out: the identification of socio-environmental damage and public health problems of the technological package; the search of alternatives for the material reproduction of families in contexts of centralization and concentration of land and capital; the construction of collective projects of rural roots; participation in political organizations; the application and translation of public policies; the influence of generational factors.